Association of JAK/STAT genetic variants with cutaneous melanoma - Gomez, Gabriela Vilas Bôas; Lourenço, Gustavo Jacob; Monteiro, Lummy Maria Oliveira; Rocha, Rafael Silva; Fernández, Kimberly Anne McGrail; Recio, Juan Angel; Torricelli, Caroline; Coser, Lilian Oliveira; Oliveira, Alexandre Leite Rodrigues; Carron, Juliana; Moraes, Aparecida Machado; Lima, Carmen Silvia Passos (Frontiers in Oncology, 2022)
Background: Janus-activated kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway regulates cutaneous melanoma (CM) development and progression. The JAK1, JAK2 and STAT3 proteins are encoded by polymorphic genes. This study aimed to verify whether single-nucleotide variants (SNVs) in JAK1 (c.1648+1272G>A, c.991-27C>T), JAK2 (c.-1132G>T, c.-139G>A) and STAT3 (c.*1671T>C, c.-1937C>G) altered risk, clinicopathological aspects, survival of CM patients, as well as protein activity. Methods: CM patients (N = 248) and controls (N = 274) were enrolled in this study. Genotyping was performed by real-time polymerase chain reaction (PCR) and JAK1, JAK2 and STAT3 expression was assessed by quantitative PCR (qPCR). STAT3 c.-1937C>G SNV was investigated by luciferase, qPCR, western blot, apoptosis, and cell cycle assays in SKMEL-28 cells with CC or GG genotype. Results: Individuals with STAT3 c.*1671TT and c.-1937CC genotypes, and TC haplotype of both SNVs were under about 2.0-fold increased risk of CM. Specific JAK1, JAK2 and STAT3 combined genotypes were associated with up to 4.0-fold increased risk of CM. Higher luciferase activity (4,013.34 vs. 2,463.32 arbitrary unit (AU); p = 0.004), STAT3 expression by qPCR (649.20 vs. 0.03 AU; p = 0.003) and western blot (1.69 vs. 1.16 AU; p = 0.01), and percentage of cells in S phase of cell cycle (57.54 vs. 30.73 %; p = 0.04) were more frequent in SKMEL-28 with STAT3 c.-1937CC than with GG genotype. CM cell line with CC genotype presented higher STAT3 protein levels than the one with GG genotype (1.93 versus 1.27 AU, p = 0.0027). Conclusion: Our data present preliminary evidence that inherited abnormalities in the JAK/STAT pathway can be used to identify individuals at a high risk of CM, who deserve additional attention for tumor prevention and early detection.